Longevity of adenovirus vector immunity in mice and its implications for vaccine efficacy. Issue 45 (29th October 2018) - Sayedahmed, Ekramy E.; Kumari, Rashmi; Shukla, Shruti; Hassan, Ahmed O.; Mohammed, Sulma I.; York, Ian A.; Gangappa, Shivaprakash; Sambhara, Suryaprakash; Mittal, Suresh K.
Abstract: There is a high incidence of adenovirus (AdV) infection in humans due to the presence of more than 60 types of human adenoviruses (HAdVs). The majority of individuals are exposed to one or more HAdV types early in their lives, leading to the development of AdV type-specific neutralizing antibodies. Similarly, immunization or gene therapy with AdV vectors leads to immune responses to the AdV vector. This 'vector immunity' is a concern for AdV vector-based applications for vaccines or gene therapy, especially when the repeated administration of a vector is required. The objective of this investigation was to establish whether AdV neutralizing antibody titers decline sufficiently in a year to permit annual vaccination with the same AdV vector. Naïve or human adenoviral vector group C, type 5 (HAdV-C5)-primed mice were mock-inoculated (with PBS) or inoculated i.m. with 10 8 PFU of either HAd-GFP [HAdV-C5 vector expressing the green fluorescent protein (GFP)] to mimic the conditions for the first inoculation with an AdV vector-based vaccine. At 1, 3, 6, and 10 months post-HAd-GFP inoculation, naïve- or HAdV-primed animals were vaccinated i.m. with 10 8 PFU of HAd-H5HA [HAdV-C5 vector expressing hemagglutinin (HA) of H5N1 influenza virus]. There was a significant continual decrease in vector immunity titers with time, thereby leading to significant continual increases in the levels of HA-specific humoral and cell-mediated immune responses. In addition, significant improvement in protection efficacy against challenge with an antigenically heterologous H5N1 virus was observed in HAdV-primed animals at 6 months and onwards. These results indicate that the annual immunization with the same AdV vector may be effective due to a significant decline in vector immunity.